Minor oral surgery in a patient with a combined fracture and congenital malformation of the first cervical vertebra. (13th May 2013) - O'Neill, F.; Thayer, T.; Balmer, M.C.; Begley, A.
Abstract Here we present a case study of a patient who presented with both a congenital failure of fusion of the posterior arch of the atlas and a concomitant Jefferson fracture of the anterior arch following trauma. This patient required minor oral surgery prior to open reduction and internal fixation of the fracture, and the considerations are discussed.